2020
DOI: 10.1371/journal.pone.0231207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of confinement in vehicle trunks on decomposition and entomological colonization of carcasses

Abstract: In order to investigate the impact of confinement in a car trunk on decomposition and insect colonization of carcasses, three freshly killed pig (Sus scrofa domesticus Erxleben) carcasses were placed individually in the trunks of older model cars and deployed in a forested area in the southwestern region of British Columbia, Canada, together with three freshly killed carcasses which were exposed in insect-accessible protective cages in the same forest. Decomposition rate and insect colonization of all carcasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This investigation found even with vehicle color accounted for, sealed cabin temperatures can dramatically exceed the environmental ones [33]. The Australian and Canadian experiments both noted accelerated decomposition catalyzed by higher temperatures within the cars, compared to outer ambient temperatures [5,31]. The ratio of pupae to adult flies remaining trapped within the vehicle led Malainey & Anderson [31] to conclude the adult flies were likely incapable of egress from the space.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This investigation found even with vehicle color accounted for, sealed cabin temperatures can dramatically exceed the environmental ones [33]. The Australian and Canadian experiments both noted accelerated decomposition catalyzed by higher temperatures within the cars, compared to outer ambient temperatures [5,31]. The ratio of pupae to adult flies remaining trapped within the vehicle led Malainey & Anderson [31] to conclude the adult flies were likely incapable of egress from the space.…”
Section: Discussionmentioning
confidence: 84%
“…Carrion concealed or within a confined space can present a barrier to primary colonization by calliphorids. Field trials of Sus scrofa concealed in automobile trunks in Louisiana, USA and Vancouver, Canada demonstrated delayed colonization by 3 days and 3-6 days, respectively [5,31]. Australian field trials of S. scrofa in the car driver's seat demonstrated delayed colonization by ~1 day [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have demonstrated that clothed carcasses have a faster decomposition rate due to greater insect diversity and feeding activity than unclothed carcasses [22][23][24]. However, some studies have reported contrasting results that clothing affects insect activities negatively and hence delays the decomposition process [22,25]. The inconsistency and paucity of data detailing insect activities associated with clothed and unclothed carcasses in tropical climates remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of this and other access factors, e.g. burial, being indoor and being in a suitcase [3,4], have not been studied in any depth in Europe. In this context, the present study reports the case of a homeless man whose corpse was found outdoors, wrapped up to the neck in a blanket.…”
Section: Introductionmentioning
confidence: 99%